Grinding fluid

JP7628363B2Active Publication Date: 2025-02-10DISCO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020114784
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-02
Publication Date
2025-02-10
Estimated Expiration
2040-07-02

AI Technical Summary

Technical Problem

When using a polishing liquid containing only hydrolyzable inorganic salts in the prior art, the polishing rate is low, and the abrasive particles are easily contaminated by the equipment and workpieces.

Method used

A polishing liquid is used, which contains hydrolyzable inorganic salts and organic alkalis, specifically strong alkali cations and weak acid anions, with concentrations of 0.50 wt% and 0.025 wt% or more, respectively, and does not contain abrasive particles.

Benefits of technology

The polishing rate is improved, the abrasive particles are contaminated on the equipment and workpieces, and the long-term effectiveness of the polishing liquid is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628363000003
    Figure 0007628363000003
  • Figure 0007628363000004
    Figure 0007628363000004
  • Figure 0007628363000005
    Figure 0007628363000005
Patent Text Reader

Abstract

To provide a polishing liquid capable of improving the polishing rate as compared with a case in which an aqueous solution in which only an inorganic salt showing alkalinity is dissolved by hydrolysis is used as a polishing liquid.SOLUTION: There is provided a polishing liquid that is used when polishing one side of a wafer using a fixed abrasive grain polishing pad with abrasive grains fixed in the pad, and in which inorganic salts showing alkalinity and organic alkali are dissolved by hydrolysis and that do not contain abrasive grains. Preferably, the inorganic salt includes a strong alkaline cation and a weak acid anion, and the organic alkali includes one or more of ammonia, amines, and basic amino acids.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing liquid used in polishing a wafer. [Background technology]

[0002] Device chips are mounted on electronic devices such as mobile phones and personal computers. Device chips are manufactured, for example, by processing silicon wafers on which devices such as ICs (Integrated Circuits) and LSIs (Large Scale Integration) are formed on the front surface.

[0003] Specifically, first, a grinding device is used to roughly grind the back side of the wafer, and then the back side is finish-ground to thin the wafer to a predetermined thickness (see, for example, Patent Document 1). Normally, in the grinding process, grinding marks (saw marks) remain on the ground surface, so after the grinding process, a CMP (Chemical Mechanical Polishing) device is used to polish the back side of the wafer to remove the saw marks (see, for example, Patent Document 2). After the polishing process, a cutting device is used to divide the wafer into multiple device chips.

[0004] To explain an example of a polishing apparatus (a face-down type polishing the lower surface side of a wafer), the polishing apparatus has a circular platen that can rotate around a rotation axis that is approximately parallel to the vertical direction. A disk-shaped polishing pad is fixed to the upper surface of the platen. As the polishing pad, for example, a fixed abrasive polishing pad containing abrasive grains is used. In addition, a nozzle for supplying a polishing liquid is disposed above the fixed abrasive polishing pad.

[0005] A disk-shaped carrier that can rotate about an axis of rotation that is approximately parallel to the vertical direction and can hold a wafer by suction is disposed above the fixed-abrasive polishing pad in a region different from the nozzle. When polishing a wafer, first, the upper side of the wafer is held by the holding surface of the carrier.

[0006] A polishing liquid is supplied to the upper surface of the rotating fixed abrasive polishing pad, and the lower surface of the wafer is pressed against the upper surface of the fixed abrasive polishing pad while rotating the wafer. The lower surface of the wafer is polished by chemical and mechanical actions between the lower surface of the wafer and the upper surface of the fixed abrasive polishing pad containing the polishing liquid. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-288881 A [Patent Document 2] Japanese Patent Application Publication No. 8-99265 Summary of the Invention [Problem to be solved by the invention]

[0008] As the polishing liquid, for example, an aqueous solution in which an inorganic salt that becomes alkaline by hydrolysis is dissolved is used. However, when an aqueous solution in which only the inorganic salt is dissolved is used as the polishing liquid, there is a problem that the polishing rate (i.e., the thickness of the wafer removed per unit time) is relatively low.

[0009] The present invention has been made in consideration of such problems, and provides a polishing liquid that can improve the polishing rate compared to the case where an aqueous solution in which only inorganic salts that become alkaline upon hydrolysis are dissolved is used as the polishing liquid. [Means for solving the problem]

[0010] According to one aspect of the present invention, there is provided a polishing liquid for use in polishing one side of a wafer using a fixed abrasive polishing pad having abrasive grains fixed in the pad, the polishing liquid comprising an inorganic salt that exhibits alkalinity upon hydrolysis; Propanediamine A polishing liquid is provided in which the above-mentioned and the above-mentioned are dissolved and which does not contain abrasive grains.

[0011] Preferably, the inorganic salt comprises a cation of a strong alkali and an anion of a weak acid. R .

[0012] Also preferably, the inorganic salt Concentration of is 0.50wt% or more, Propanediamine concentration is 0.025wt% or more 。 Effect of the Invention

[0013] In the polishing liquid according to one embodiment of the present invention, inorganic salts that become alkaline by hydrolysis and organic alkalis are dissolved. The action of inorganic salts and organic alkalis can improve the polishing rate compared to the case where an aqueous solution in which only inorganic salts that become alkaline by hydrolysis are dissolved is used as the polishing liquid. Furthermore, since the polishing liquid does not contain abrasive grains, there is an advantage that the inside of the device and the workpiece are not contaminated by abrasive grains as in the case where free abrasive grains are used. [Brief description of the drawings]

[0014] [Figure 1] 1 is a cross-sectional view showing an overview of a polishing apparatus. [Diagram 2] 1 is a graph showing the polishing rate and the surface roughness of the polished surface of a wafer. [Diagram 3] 1 is a graph showing the polishing rate when the weight ratio of an organic alkali to an inorganic salt is changed. [Figure 4] 1 is a graph showing the change in polishing rate when polishing for 5 minutes is repeated 10 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment according to one aspect of the present invention will be described with reference to the attached drawings. First, a polishing liquid used in this embodiment will be described. Note that this embodiment is premised on the use of a fixed-abrasive polishing pad in which abrasive grains are fixed in the polishing pad.

[0016] Conventionally, the polishing liquid for fixed abrasive polishing pads does not contain abrasive grains, and only inorganic salts that become alkaline by hydrolysis are dissolved in the liquid. When such a polishing liquid is used, the fixed abrasive polishing pad is less likely to become clogged with polishing debris, and this has the advantage that the polishing rate (thickness of the wafer removed per unit time) is less likely to decrease over time.

[0017] However, the polishing liquid has a disadvantage that the polishing rate is relatively low to begin with. Therefore, the polishing liquid has a higher chemical etching effect than a polishing liquid in which only inorganic salts are dissolved. of In order to increase the polishing efficiency, it is possible to use a polishing liquid in which an organic alkali is dissolved instead of the inorganic salt.

[0018] However, when a polishing liquid for a fixed abrasive polishing pad is used that does not contain abrasive grains and contains only an organic alkali, the polishing waste blocks the pores of the fixed abrasive polishing pad, which reduces the retention ability of the fixed abrasive polishing pad to retain the polishing liquid in the pad, and therefore the polishing rate is likely to decrease over time.

[0019] In view of the above, the applicant of the present application has conceived that by using an inorganic salt and an organic alkali in combination, it may be possible to compensate for the disadvantages of the inorganic salt with the advantages of the organic alkali, and vice versa.

[0020] In other words, it was thought that by using an inorganic salt and an organic alkali in combination, the polishing rate would be higher than when only an inorganic salt was used, and the polishing rate would be less likely to decrease over time than when only an organic alkali was used.

[0021] (Polishing Liquid) The polishing liquid of this embodiment is a mixture of an inorganic salt that becomes alkaline when hydrolyzed in pure water and an organic alkali. Or ammonia In particular, the inorganic salt is preferably 0.50 wt % or more and the organic alkali is preferably 0.025 wt % or more, as will be described later.

[0022] The inorganic salt is a water-soluble salt, for example, a salt represented by the general formula: M(OH) n (where M is a cation M n+ where n is an integer of 1 or greater) and a weak acid anion.

[0023] As the cations of strong alkali, cations of alkali metals such as potassium ion, sodium ion, etc., and cations of alkaline earth metals such as calcium ion, barium ion, etc. are preferred. As the anions of weak acids, anions of carbonate, phosphate, oxalic acid, acetic acid, formic acid, silicic acid, etc. are preferred.

[0024] Organic alkalis are alkaline in aqueous solution. ,a The amino acid sequence includes at least one of amine and basic amino acid, such as arginine, histidine, and lysine.

[0025] As the amine, for example, a water-soluble organic compound such as an aliphatic amine or a heterocyclic amine can be used. As the aliphatic amine, ethylenediamine, propanediamine, butanediamine, pentanediamine, hexanediamine, diethylenetriamine, tris(2-aminoethyl)amine, etc. can be used. Furthermore, as the heterocyclic amine, piperazine, imidazole, etc. can be used.

[0026] Next, an experiment for identifying the optimum weight ratio of inorganic salt and organic alkali for polishing will be described. In this experiment, a silicon wafer (bare wafer) on which no devices or the like are formed was polished by the polishing apparatus 2. Here, an overview of the polishing apparatus 2 used in the experiment will be described.

[0027] Fig. 1 is a cross-sectional view showing an overview of a face-up type polishing apparatus 2 for polishing the upper surface side of a wafer 11. The Z-axis direction shown in Fig. 1 is approximately parallel to the vertical direction. The polishing apparatus 2 has a disk-shaped chuck table 4.

[0028] The upper end of a cylindrical rotating shaft (not shown) arranged substantially parallel to the Z-axis direction is connected to the lower part of the chuck table 4. The output shaft of a rotation drive source (not shown) such as a motor is connected to the lower end of the rotating shaft. When the rotation drive source is operated, the chuck table 4 rotates around the rotating shaft in a predetermined direction.

[0029] The chuck table 4 has a disk-shaped frame 6 made of a metal such as stainless steel. A disk-shaped recess is formed in the upper part of the frame 6, and a disk-shaped porous plate 8 made of porous ceramics or the like is fixed in this recess.

[0030] The upper surface of the porous plate 8 and the upper surface of the frame 6 are flush with each other to form a substantially flat holding surface 4a. Below the porous plate 8, a plurality of first flow paths 6a are formed in a radial direction of the frame 6. Note that one first flow path 6a is shown in FIG.

[0031] Furthermore, a second flow passage 6b is formed in the radial center of the frame 6 along the Z-axis direction. An upper end of the second flow passage 6b is connected to the first flow passage 6a, and a lower end of the second flow passage 6b is connected to a suction source (not shown) such as an ejector. When the suction source is operated, a negative pressure is transmitted to the upper surface of the porous plate 8.

[0032] The wafer 11 placed on the holding surface 4a is sucked and held by the negative pressure generated on the holding surface 4a. A polishing unit 10 is disposed above the holding surface 4a. The polishing unit 10 has a cylindrical spindle housing (not shown).

[0033] A cylindrical spindle 12 is rotatably accommodated within the spindle housing. The longitudinal direction of the spindle 12 is disposed substantially parallel to the Z-axis direction. A motor (not shown) that rotates the spindle 12 is connected to the upper end of the spindle 12.

[0034] The center of the upper surface of a disk-shaped mount 14 is connected to the lower end of the spindle 12. The mount 14 has a diameter larger than that of the wafer 11. A disk-shaped polishing wheel 16 having approximately the same diameter as the mount 14 is attached to the lower surface of the mount 14.

[0035] The grinding wheel 16 has a disk-shaped wheel base 18 connected to the underside of the mount 14. The wheel base 18 is made of a metal such as aluminum or stainless steel. A grinding pad 20 having approximately the same diameter as the wheel base 18 is fixed to the underside of the wheel base 18.

[0036] The polishing pad 20 is a fixed abrasive polishing pad in which abrasive grains are fixed in the pad. The polishing pad 20 can be manufactured by impregnating a urethane solution in which abrasive grains of μm order size are dispersed into a polyester nonwoven fabric, and then drying the same.

[0037] The abrasive grains are formed of materials such as silica (silicon oxide), silicon carbide, cBN (cubic boron nitride), diamond, metal oxide fine particles, etc. Examples of metal oxide fine particles used in the abrasive grains include ceria (cerium oxide), zirconia (zirconium oxide), alumina (aluminum oxide), etc.

[0038] The radial center positions of the polishing pad 20, the wheel base 18, the mount 14, and the spindle 12 are approximately aligned, and a cylindrical through-hole 22 is formed so as to pass through these centers. A pipe (not shown) of a polishing liquid supply source (not shown) is connected to the upper end of the through-hole 22.

[0039] The polishing liquid supply source includes a pipe, a liquid pump, and a storage tank for the polishing liquid 24. The polishing liquid supply source supplies the polishing liquid 24 to the through opening of the polishing pad 20 via the through hole 22. The polishing liquid 24 does not contain abrasive grains.

[0040] Using the polishing liquid 24 that does not contain abrasive grains has the advantage that, unlike using a polishing liquid that contains abrasive grains (i.e., free abrasive grains), the inside of the polishing apparatus 2 and the workpiece, the wafer 11, can be prevented from being contaminated with abrasive grains.

[0041] A Z-axis direction moving unit (not shown) is connected to the spindle housing. By pushing the polishing unit 10 downward with the Z-axis direction moving unit, the polishing pad 20 can press the wafer 11, which is suction-held on the holding surface 4a, downward with a predetermined pressure.

[0042] When polishing the wafer 11, first, the wafer 11 is suction-held by the holding surface 4a, and then the chuck table 4 is rotated in a predetermined direction, and the spindle 12 is rotated in a predetermined direction.

[0043] At this time, when the polishing pad 20 is pressed downward with a predetermined pressure while the polishing liquid 24 is being supplied from the polishing liquid supply source, the upper surface side of the wafer 11 is polished by the chemical and mechanical action between the upper surface (one surface) side of the wafer 11 and the lower surface side of the polishing pad 20 containing the polishing liquid 24.

[0044] Next, the optimum concentration of inorganic salt in the experiment will be described. Fig. 2 is a graph showing the polishing rate (μm / min) and the roughness Ra (Å) of the polished surface of the wafer 11 when the concentration of potassium carbonate is set to various values ​​(0.10 wt%, 0.30 wt%, 0.50 wt%, 0.70 wt%, and 1.00 wt%).

[0045] The bar graphs show the removal rate (μm / min) located on the left side of the vertical axis in Figure 2. The removal rate when polishing for 5 minutes is shown in the shaded bar, and the removal rate when polishing for 2 minutes is shown in the open bar.

[0046] The line graph shows the roughness Ra (Å) of the polished surface of the wafer 11 (i.e., the upper surface of the wafer 11) located to the right of the vertical axis in Figure 2. Ra means the arithmetic mean roughness, and its unit is angstroms.

[0047] The roughness Ra of the polished surface is data obtained using a face-down type polishing apparatus, not the face-up type polishing apparatus 2 shown in Fig. 1. However, the tendency of the roughness Ra relative to the potassium carbonate concentration (i.e., the higher the potassium carbonate concentration, the larger the roughness Ra) is also the case with the face-up type.

[0048] Silica abrasive grains were used as the abrasive grains of the polishing pad 20. In the experiment, the rotation speed of the spindle 12 was set to 95 rpm, and the rotation speed of the chuck table 4 was set to 90 rpm. The pressing force against the wafer 11 was set to 29.4 kPa.

[0049] The polishing liquid was an aqueous solution of potassium carbonate (K2CO3) containing no abrasive grains and prepared by dissolving powdered potassium carbonate in pure water, which was supplied from a polishing liquid supply source at a flow rate of 0.5 L / min. The polishing time was 900 seconds (i.e., 15 minutes).

[0050] 2, when the concentration of potassium carbonate was 0.50 wt% or more, the polishing rate became substantially constant. Therefore, it is preferable that the concentration of potassium carbonate is 0.50 wt% or more. However, the higher the concentration of potassium carbonate, the larger the roughness Ra.

[0051] Therefore, in the range of 0.10 wt% or more and 1.00 wt% or less, in order to suppress the roughness Ra and increase the polishing rate, it is preferable to set the potassium carbonate concentration to be close to 0.50 wt% in the range of 0.50 wt% or more.

[0052] Based on these results, we next created a polishing solution 24 containing an inorganic salt (0.50 wt% potassium carbonate) and various concentrations of an organic alkali (1,3-propanediamine (hereinafter simply referred to as propanediamine)), and investigated the difference in polishing rate depending on the concentration of the organic alkali.

[0053] 3 is a graph showing the polishing rate when the weight percentage of organic alkali (propanediamine) relative to inorganic salt (potassium carbonate) is changed. The horizontal axis shows the type of polishing liquid as shown in Table 1 below, and the vertical axis shows the polishing rate (μm / min). The polishing rate when polishing for 5 minutes is shown in the shaded bar, and the polishing rate when polishing for 2 minutes is shown in the white bar.

[0054] Silica abrasive grains were used as the abrasive grains of the polishing pad 20. In Comparative Example 1, Comparative Example 2, and Experimental Example 1 to Experimental Example 8, the rotation speed of the spindle 12 was set to 500 rpm, and the rotation speed of the chuck table 4 was set to 505 rpm. The pressing force on the wafer 11 was set to 25 kPa.

[0055] Comparative Example 1 shows the experimental results of polishing a wafer 11 using an alkaline aqueous solution containing no abrasive grains and in which only 0.50 wt % potassium carbonate was dissolved in pure water, which was supplied from a polishing liquid supply source at a flow rate of 0.15 L / min.

[0056] Comparative Example 2 shows the experimental results of polishing a wafer 11 using an alkaline aqueous solution containing no abrasive grains and in which only 0.10 wt % propanediamine was dissolved in pure water, which was supplied from a polishing liquid supply source at a flow rate of 0.15 L / min.

[0057] In contrast, the polishing liquid 24 used in Experimental Examples 1 to 8 does not contain abrasive grains, and is an alkaline aqueous solution in which powdered potassium carbonate and liquid propanediamine are dissolved in pure water.

[0058] Experimental Examples 1 to 8 are experimental results in which the polishing liquid 24 was supplied from the polishing liquid supply source at a flow rate of 0.15 L / min to polish the wafer 11. The pH of the polishing liquid 24 in Experimental Examples 1 to 8 was 10 or more and 14 or less.

[0059] Table 1 shows the potassium carbonate concentration (wt%), propanediamine concentration (wt%), polishing rate (μm / min) when polishing for 5 minutes, and polishing rate (μm / min) when polishing for 2 minutes in Comparative Example 1, Comparative Example 2, and Experimental Example 1 to Experimental Example 8.

[0060] [Table 1]

[0061] In both the 5-minute polishing and the 2-minute polishing, the polishing rates of Experimental Examples 1 to 8 are higher than that of Comparative Example 1. Considering that the polishing rate remained substantially constant even when the potassium carbonate concentration was 0.50 wt% or more in the experiment shown in Fig. 2 described above, it can be said that the polishing rate can be improved by the action of inorganic salts and organic alkalis compared to the case where an aqueous solution in which only inorganic salts that exhibit alkalinity due to hydrolysis are dissolved is used as the polishing liquid.

[0062] Moreover, the polishing rates of Experimental Examples 2 to 8 were higher in both the 2-minute polishing and the 5-minute polishing than the polishing rate of Comparative Example 2. Therefore, it is preferable to set the propanediamine concentration to 0.025 wt % or more.

[0063] However, since the polishing rate tends to increase with an increase in the propanediamine concentration, the inorganic salt (potassium carbonate) may be set to 0.50 wt % or more and the organic alkali (propanediamine) may be set to 0.050 wt % or more.

[0064] Also, the inorganic salt may be 0.50 wt % or more and the organic alkali may be 0.075 wt % or more, or the inorganic salt may be 0.50 wt % or more and the organic alkali may be 0.10 wt % or more.

[0065] The polishing rate tended to increase with increasing propanediamine concentration, but in both the 2-minute and 5-minute polishing cases, in Experimental Examples 6 to 8, there was no clear tendency for the polishing rate to increase.

[0066] Therefore, when the concentration of the inorganic salt (potassium carbonate) is 0.50 wt% or more and the concentration of the organic alkali (propanediamine) is 0.15 wt% or more, in order to reduce chemical costs and increase the polishing rate, it is desirable to keep the concentration of the organic alkali close to 0.15 wt% within the range of 0.15 wt% or more.

[0067] Next, we will examine whether the use of inorganic salts and organic alkalis makes the polishing rate less likely to decrease over time than the use of only organic alkalis. Figure 4 is a line graph showing the change in the polishing rate when polishing for 5 minutes was repeated 10 times.

[0068] The vertical axis indicates the polishing rate (μm / min), and the horizontal axis indicates the number of times (1 to 10 times). Graph A1 shows the change in the polishing rate after 10 polishings when the potassium carbonate concentration is 0.50 wt%. Graph A2 shows the change in the polishing rate after 10 polishings when the propanediamine concentration is 0.15 wt%.

[0069] Furthermore, graph A3 shows the change in polishing rate in 10 polishing cycles when the potassium carbonate concentration was 0.50 wt% and the propanediamine concentration was 0.15 wt%. Each polishing cycle lasted for 5 minutes.

[0070] In each round, the wafer 11 was polished under the same conditions as in the experiment in Fig. 3 (spindle 12 rotation speed 500 rpm, chuck table 4 rotation speed 505 rpm, pressing force on the wafer 11 25 kPa, polishing liquid supply rate 0.15 L / min). Although it overlaps with the information in Fig. 4, the polishing rate values ​​of graphs A1 to A3 are shown in Table 2.

[0071] [Table 2]

[0072] As is clear from FIG. 4 and Table 2, in the case of graph A1 (potassium carbonate 0.50 wt%), the polishing rate is lower than those of graphs A2 and A3, but the polishing rate did not decrease even after 10 polishings (i.e., 5 minutes × 10 polishings = 50 minutes).

[0073] Furthermore, the applicant has confirmed by observing the polishing pad 20 after use that when an aqueous potassium carbonate solution is used as the polishing liquid, there is very little polishing debris adhering to the polishing pad 20 after use.

[0074] The adhesion of polishing debris is thought to be closely related to the polishing rate, and the reason why there is no decrease in the polishing rate over time in graph A1 is thought to be because clogging of the polishing pad 20 does not easily occur.

[0075] In contrast, in the case of graph A2 (0.15 wt% propanediamine), the polishing rate was higher than that of graph A1, but the polishing rate was approximately constant in the seventh and eighth polishings, and the polishing rate decreased in the ninth and tenth polishings compared to the seventh and eighth polishings.

[0076] The decrease in the polishing rate over time shown in graph A2 is believed to be due to the polishing debris clogging the pores of the polishing pad 20, as described above, reducing the polishing pad 20's ability to retain polishing liquid within the pad.

[0077] In fact, the applicant has confirmed that when a propanediamine aqueous solution is used as the polishing liquid, the amount of polishing debris adhering to the polishing pad 20 after use is much greater than when a potassium carbonate aqueous solution is used as the polishing liquid.

[0078] In the case of graph A3 (potassium carbonate 0.50 wt % and propanediamine 0.15 wt %), the polishing rate was higher than that of graph A2, and the polishing rate did not decrease even after 10 polishings.

[0079] In this way, by using an inorganic salt and an organic alkali, the polishing rate was increased compared to when only an inorganic salt was used, and the decrease in the polishing rate over time was suppressed compared to when only an organic alkali was used.

[0080] In the experiment shown in FIG. 4 and Table 2, potassium carbonate was used as the inorganic salt and propanediamine was used as the organic alkali. However, it is presumed that similar effects would be obtained when using other inorganic salts that are considered to have the same effect as potassium carbonate during polishing and other organic alkalis that are considered to have the same effect as propanediamine during polishing.

[0081] In addition, the structures, methods, etc. according to the above-described embodiments can be modified as appropriate without departing from the scope of the object of the present invention. [Explanation of symbols]

[0082] 2: Polishing device 4: Chuck table 4a: Holding surface 6: Frame 6a: First flow path 6b: Second flow path 8: Porous plate 10: Polishing unit 11: Wafer 12: Spindle 14: Mount 16: Abrasive wheel 18: Wheel base 20: Polishing pad 22: Through hole 24: Polishing liquid

Claims

1. A polishing liquid used when polishing one side of a wafer using a fixed abrasive polishing pad having abrasive grains fixed in the pad, comprising: A polishing liquid characterized in that it contains dissolved inorganic salts that become alkaline upon hydrolysis and propanediamine, and does not contain abrasive grains.

2. 2. The polishing liquid according to claim 1, wherein said inorganic salt comprises a cation of a strong alkali and an anion of a weak acid.

3. The concentration of the inorganic salt is 0.50 wt % or more; 3. The polishing liquid according to claim 1, wherein the concentration of the propanediamine is 0.025 wt % or more.

Citation Information

Patent Citations

  • Polishing device

    JP1996099265A

  • Grinding apparatus and grinding method

    JP2000288881A

  • Alkali metal-containing polishing system and method

    JP2004529488A

  • Chemical mechanical polishing system and its using method

    JP2006287244A

  • CMP of copper / ruthenium substrates

    JP2009514219A